The Emancipation of Women in the Balkans in the 19th and 20th Centuries: Contrastive Analysis of the Role of Serbian and Sephardic Women in the Modernization Process (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
In the second half of the 19th century significant socio-economic changes occurred in the whole Europe as a result of the bourgeois revolution. The need for change in lifestyle was also present in the Balkans and it was followed by a period of social modernization and emancipation in various fields. This paper focuses on the status of women and their role in a social change in the Serbian majority community, as well as in the minority Sephardic community in Serbia. The paper presents three theses which authors verify through theoretical study: that both Serbian and Sephardic women took an active part in the modernization of Serbian society, entering new roles and fighting for liberation from patriarchal constraints and thereby contributing to the emancipation and more equal position of women in society; that the emancipation was only partially achieved – Serbian and Sephardic women did gain more rights in certain areas of life, but patriarchal ideas and subordination of women were still dominanant; and that the lifestyle of Jewish women was not much different from the lifestyle of Serbian women because of similar social patterns which shaped their lives over history and made the process of their emancipation quite similar, except for the fact that there were additional obstacles that Sephardic women had to overcome in the process of emancipation.
Keywords: modernization process; patriarchal patterns; Sephardic women; Serbian women; women's emancipation